Compensation Determination Analysis Using Hay Job Evaluation Method - Dimas Baswara; Dinda Kristiana; Erwina Syahputri; Helen Laelita Putri; Mellisa Ardila (Ridwan Institute, 2022)
This study focuses on the financial compensation of employees at PT ABC by using the data on direct and indirect compensation provided. The data used includes basic salary and other benefits. The purpose of this study was to identify the salary and compensation system at PT ABC. Develop job grading and job values ??based on the Hay System method at PT ABC. Analyze and evaluate the improvement of the appropriate salary and compensation system at PT ABC. The method used in this research is the point system method, which is the point method for assigning numerical values ??to certain job factors and the total value providing a quantitative assessment. From the existing data on the basic salary of 43 employees at UKM ABC, which is compared to the Lampung UMP of Rp. 2,431,324 and the Bandar Lampung UMK of Rp. 2,739,983, the results are shown in the figure above. The graph shows that the total salary paid to all employees of PT. ABC is already above the Lampung UMP and Bandar Lampung UMK. Based on the results of research and analysis that has been carried out, it can be concluded that PT ABC Lampung City has four levels in the compensation system based on the hierarchy contained in its organizational structure. At level four there is one job title, namely branch head, at level three there are three job titles occupied by supervisor positions, at level two there are three job titles, namely the position of deputy supervisor, and at level one occupied by twenty-one job titles, namely staff